Effect of Na2WO4 addition on formation mechanism and microstructure of micro-arc oxidation coating on Al-Ti double-layer composite plate. (May 2020) - Chen, Quanzhi; Li, Weizhou; Ling, Kui; Yang, Ruixia
Abstract: Micro-arc oxidation (MAO) coating was produced on the surface of Al-Ti double-layer composite plate. Different concentrations of 0–8 g/L Na2 WO4 were added into the MAO electrolyte and its effects on the MAO behavior and coating microstructure were investigated. The results showed that the addition of Na2 WO4 enhanced the MAO reaction intensity on the part of Al alloy (P-Al) in the Al-Ti composite plate and correspondingly increased the coating thickness, while the reaction intensity and coating thickness on the part of Ti alloy (P-Ti) was decreased. XRD analysis confirmed a formation of WO3 in both side coatings of the composite plate, and W 6+ was detected similarly by XPS spectra. SEM observations indicated that the surface porosity and thickness of the P-Ti coating was reduced, while those of the P-Al coating was increased with the increase of Na2 WO4 concentration. TEM analysis verified that corresponding oxide phases and WO3 were formed in the different MAO coatings on the P-Al or the P-Ti and the addition of Na2 WO4 enhanced the coating compactness of the transition zone. EDX detection proved that W concentration in the P-Ti coating was higher than that in the P-Al coating. The nano-indentation tests showed that the hardness and Young's modulus of both side coatings were improved with adding Na2 WO4 . A competitive mechanism was proposed for the MAO process with the addition of Na2 WO4, and the distribution of electrical energy was found to be balanced in both sides of composite plate. Graphical abstract: Unlabelled Image Highlights: The electrical energy distribution during the MAO process of Al-Ti double-layer composite plate was analyzed. The distribution of electrical energy on the Al-Ti double-layer composite plate surface was improved with adding the Na2 WO4 . The addition of Na2 WO4 could improve the structure of MAO coating. The influence mechanism of Na2 WO4 on the MAO behavior was summarized.